Inteligência artificial, machine learning e algoritmos : como estas tecnologias estão moldando o novo mercado da música - Santos, João Marcos Abreu dos (2019)
This research project explores the impacts of technology on music market, with an emphasis on the influence of Artificial Intelligence, Algorithms and Machine Learning, and how these technologies are shaping the future of music and developing new hits. The chapters are divided into blocks that include story about the quest for success songs, music and cognition and the use of algorithms and Artificial Intelligence in people's behavior data of music for greater accuracy to lunch a potential hit. As far as applicability is concerned, this study contributes to an analysis of which paths the industry will follow, which tools will have importance in this new scenario, and the consequences of the eternal struggle between art and market. It is therefore a document for professionals, musicians, composers, producers and all stakeholders involved in the music chain and who make this activity their livelihood